Short-Term Trends in Economic Burden and Catastrophic Costs of Type 2 Diabetes Mellitus in Rural Southwest China - Hui-fang Li; Le Cai; Allison Rabkin Golden (Journal of Diabetes Research)
Objectives. This study is aimed at gaining insights on the changing prevalence, economic burden, and catastrophic costs of diabetes in rural southwest China. Materials and Methods. Data were collected from two cross-sectional health interviews and examination surveys among individuals aged≥35 years in rural Yunnan Province. A prevalence-based cost-of-illness method was used to estimate the cost of diabetes. Information about the participants’ demographic characteristics and economic consequences of diabetes was obtained using a standard questionnaire. Fasting blood sugar levels were recorded for each study participant. Results. During the study period, the overall prevalence of diabetes increased from 7.7% to 9.5% (P<0.01) and the economic cost of diabetes increased 1.52-fold. The largest increases were observed in hospital costs (1.77-fold increase), while unit medication costs fell by 18.6%. Both in 2009 and in 2016, males had higher overall direct and indirect costs of diabetes than females (P<0.05). Direct costs represented the largest component of economic cost of diabetes while hospital costs were the main drivers of direct medical expenditures, accounting for 66.2% of the total direct costs in 2009 and 75.9% in 2016. The incidence of household catastrophic health payment and household impoverishment due to diabetes was 24.0% and 17.9% in 2009 and 23.6% and 17.6% in 2016, respectively. These rates did not differ between the two survey years (P>0.05). Conclusions. The prevalence and economic burden of diabetes increased substantially from 2009 to 2016 in rural southwest China. The findings underscore an urgent need for the government to invest more financial resources in the prevention of diabetes and improvement of access to affordable medication in rural southwest China.